Clinico-radiological assessment of vascularized muscle pedicle bone graft in scaphoid non-union - Bhatnagar, Rachit; Chaurasia, Tushar; Singh, Aseem P. (International Journal of Research in Orthopaedics, 2024)
Background: The aim of this study was to assess the clinico-radiological outcome of vascularised muscle pedicle bone graft in scaphoid non-union. Methods: 16 men and 8 women with non-union of the scaphoid involving the proximal pole (n=6), waist (n=14), and distal pole (n=4) were randomly assigned to receive a vascularized muscle pedicle bone transplant with Herbert screw fixation. Their ages ranged from 18 to 45 (mean 32). Eight months was the average non-union period (range: 4–12 months). Results: The mean follow-up duration was 18 months. 20 out of 24 were united. In 16 out of 24 cases, the scapholunate and radiolunate angles were corrected. 4 of 24 did not achieve union, and 3 of those were associated with proximal pole absorption. During pedicle dissection, there was no iatrogenic fracture or hardware malfunction. Conclusions: Scaphoid non-union has been successfully treated with vascularized bone grafts, particularly in cases where the non-union has an avascular proximal pole or has not healed following prior surgery.